2022
DOI: 10.3390/app122412730
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Preparation of a New High-Permeability Emulsified Asphalt and Its Modification

Abstract: Emulsified asphalt is widely used as a prime coat in road engineering, especially in pavements with cement-stabilized semi-rigid bases. The objective of this paper is to develop a new emulsified asphalt with high permeability and pulling-off strength. A new type of high-permeability emulsified asphalt was prepared by using 55.2% diluted asphalt (44.16% matrix asphalt + 11.04% diluent) + 40% emulsion (2% emulsifier + 0.5% stabilizer + 1% osmotic agent + 1% op-10 + 35.5% water) + 4.8% aromatic oil. The storage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Combined with the solid engineering, the optimal mixing amount of kerosene permeability agent is determined to be 12%. However, it does not consider the influence of emulsified asphalt with kerosene permeable agent on its own properties.Zhang X [17]Using aromatic hydrocarbon oil as a penetrant to add to the emulsified asphalt, the test shows that compared with the traditional products, the storage stability is better, and the permeability and depth are greatly improved.Shi S [18]Biomass oil was selected as penetrant, and the test structure showed that biomass oil emulsified asphalt has the best permeability performance when the ratio of biomass oil / asphalt is 1:3. Zhang X And ShiS et al chose new materials as permeable agents.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the solid engineering, the optimal mixing amount of kerosene permeability agent is determined to be 12%. However, it does not consider the influence of emulsified asphalt with kerosene permeable agent on its own properties.Zhang X [17]Using aromatic hydrocarbon oil as a penetrant to add to the emulsified asphalt, the test shows that compared with the traditional products, the storage stability is better, and the permeability and depth are greatly improved.Shi S [18]Biomass oil was selected as penetrant, and the test structure showed that biomass oil emulsified asphalt has the best permeability performance when the ratio of biomass oil / asphalt is 1:3. Zhang X And ShiS et al chose new materials as permeable agents.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, modification of emulsified asphalt is the main way to achieve the high performance of emulsified asphalt [14,15]. The emulsified asphalt modifiers commonly include Styrene Butadiene Styrene (SBS), Styrene Butadiene Rubber (SBR), and water-based epoxy resins [16,17].…”
Section: Introductionmentioning
confidence: 99%